Biodegradation of methyl tert-butyl ether by Kocuria sp. - Kiković Dragan D.; Hamidović Saud R.; Jović Jelena B.; Raičević Vera B.; Kljujev Igor S.; Lalević Blažo T. (Hemijska Industrija, 2012)
Methyl tert-butyl ether (MTBE) has been used to replace the toxic compounds from gasoline and to reduce emission of air pollutants. Due to its intensive use, MTBE has become one of the most important environment pollutants. The aim of this paper is isolation and identification of the bacteria from wastewater sample of “HIP Petrohemija” Pančevo (Serbia), capable of MTBE biodegradation. The results of the investigation showed that only the bacterial isolate 27/1 was capable of growth on MTBE. The result of sequence analyzes of 16S rDNA showed that this bacterial isolate belongs to the Kocuria sp. After the incubation period of 86 days, the degradation rates of initial MTBE concentration of 25 and 125 μg/ml were 55 and 36%, respectively. These results indicated that bacteria Kocuria sp. is successfully adapted on MTBE and can be potentially used in bioremediation of soils and waters contaminated with MTBE.